Air-to-air enthalpy exchangers: Membrane modification using metal-organic frameworks, characterisation and performance assessment. (15th April 2021) - Albdoor, Ahmed K.; Ma, Zhenjun; Cooper, Paul; Al-Ghazzawi, Fatimah; Liu, Jingjing; Richardson, Christopher; Wagner, Pawel
Abstract: Air-to-air membrane enthalpy exchanger is one of the environmentally friendly technologies that has been increasingly used in the building sector to recover the waste energy due to ventilation. In this study, we report the development of a facile approach for the deposition of a thin layer of the metal-organic frameworks (MOFs) ZIF-8 and HKUST-1 on polyvinylidene fluoride (PVDF) membranes in order to improve their water vapour transport properties. Material characterisation and properties determination were carried out for the tested membranes. It was shown that the surface hydrophilicity of the coated membranes was improved as compared to the pristine membrane. In general, the water vapour diffused through the coated membranes was higher than the pristine membrane at all the test conditions, while insignificant differences in the mechanical properties between the pristine membrane and the coated membranes were observed. The performance of the coated membranes in an air-to-air membrane enthalpy exchanger was then experimentally assessed. It was found that the effectiveness improved from 44.4% for pristine PVDF45 to 45.9% and 47.7% for the ZIF-8@PVDF45 and HKUST-1@PVDF45 membranes, respectively, at the flow rate of 0.24 L/s. This study provides a useful and facile method to enhance the performance of polymeric membranes used in air-to-air membrane enthalpy exchangers, which could potentially reduce both building energy consumption and greenhouse gas emissions. Highlights: Metal- organic framework was coated onto PVDF membrane to improve the performance. The pristine PVDF membrane was coated using the solvent evaporation method. Structural characterisations were conducted for the pristine and coated membranes. A mathematical model was developed to predict the performance of the membrane. The coating improved both the membrane hydrophilicity and moisture diffusivity.